Effect of mediterranean forest parasite with Curculio sp. on nutritional value of acorn for Iberian pig feeding and fat characteristics. - Daza, a; López-Bote, C. J.; Tomás Barberán, F. a; Espin, J. C.; López Carrasco, C.; Olivares, A.; Rey, a I. (Meat science, 2007)
Sixteen Iberian barrows of the same age with an average initial live weight of 100.1kg were randomly distributed in two groups of eight pigs each. One group was fed healthy acorns and the other group received acorns infested of Curculio sp. The subcutaneous backfat from pigs fed healthy acorns had higher C18:1n-9, MUFA and C20:5n-3 and lower C18:0 and SFA proportions than that from the pigs fed acorns infested with Curculio. The consumption of acorns infested with Curculio sp. led to a reduction of C18:1n-9, MUFA, C18:2n-6, C18:3n-3, C22:5n-3 and PUFA proportions in neutral lipids from Longissimus dorsi muscle with respect to consumption of healthy acorns, whereas in polar lipids it produced a reduction in C18:1n-9, MUFA and C18:4n-3 proportions and an increase in C18:2n-6, C20:4n-6, n-6 and C20:5n-3 proportions and of n-6/n-3 ratio with respect to the healthy acorns consumption. The pigs fed healthy acorns had higher intramuscular fat percentage in Longissimus dorsi than pigs fed with acorns infested with Curculio (9.95 vs 7.09% SEM=0.60).
The following values have no corresponding Zotero field: accession-num: 22064301
Keywords: Curculio; fat; fatty acid; iberian pig

Effects of feeding in free-range conditions or in confinement with different dietary MUFA/PUFA ratios and α-tocopheryl acetate, on antioxidants accumulation and oxidative stability in Iberian pigs. - Daza, a; Rey, a I.; Ruiz, J.; López-Bote, C. J. (Meat science, 2005)
The experiment was undertaken to provide information of the influence of feeding either free-range or in confinement with different dietary MUFA/PUFA ratios and α-tocopheryl acetate supplementation (40 vs. 200 mg/kg) on tocopherol content and susceptibility to lipid oxidation of muscle and microsomes in Iberian pigs. The grass provided to the pigs had a similar α-tocopherol concentration to that observed for diets supplemented with 200 mg/kg α-tocopheryl acetate, and acorns supplied fourfold higher content of γ-tocopherol than the experimental diets. The α- and γ-tocopherol contents of muscle reflected the tocopherol concentration of the diets. Mono and Medium diets produced a similar MUFA/PUFA ratio in neutral and polar lipids of pig muscle to those fed outdoors. The lowest TBARS numbers were found in muscle samples from pigs fed a MUFA-enriched diet in confinement. No significant influence of free-range feeding or dietary fat on drip loss was found. However, α-tocopheryl acetate supplementation reduced (P<0.05) drip loss. Dietary vitamin E supplementation decreased the membrane lipid oxidation by 18% after 120 min. However, free-range feeding decreased the extent of microsome oxidation by 20%, 56% and 82% after 120 min when compared with those groups fed in confinement with high, medium and low MUFA/PUFA ratios, respectively. The hexanal concentration of muscle showed a similar trend to that observed for microsome induced-oxidation, suggesting, that hexanal determination is a more accurate method to measure lipid oxidation in iberian pig muscle than the thiobarbituric acid test.
The following values have no corresponding Zotero field: accession-num: 22062651
Keywords: a- and c-tocopherols; dietary fat; free-range feeding; lipid oxidation; microsomes